EXAMPLE-BASED LEARNING: DEVELOPMENT OF BUSINESS APPLICATIONS WITH .NET TECHNOLOGIES - Gestal, Marcos (2015)
For a long time, J2EE has been the dominating framework for the development of business applications. This fact resulted in a rich ecosystem of tools, manuals, tutorials, etc. that explain different implementation alternatives or peculiarities. The incursion of .NET Framework in the business environment has generated a strong demand of application implementation under this architecture. However, the quantity and quality of documents available significantly differs from its main alternative (J2EE). This documentation gap is especially visible and worrying when the objective is to teach the concepts of Framework, from a teacher’s point of view, to the future graduates of the Information Systems Engineering program. This paper describes the teaching approach used in order to achieve the goal of having the students become familiar with this alternative framework and the usual model practices within it. Thus, it is based mainly on a set of basic tutorials that show the foundations of technology and two complete applications (miniportal and minibank) explaining how to apply design patterns when developing a business solution.